1978
DOI: 10.1136/hrt.40.5.552
|View full text |Cite
|
Sign up to set email alerts
|

Significance of left anterior hemiblock.

Abstract: SUMMARY To determine the relation between left anterior hemiblock and cardiovascular abnormalities in an ambulatory population, the clinical records and electrocardiograms of 16 600 male applicants for life insurance between 1966 and 1974 were reviewed. There were 413 applicants with left anterior hemiblock; they were compared with an age-matched control group. The subjects with left anterior hemiblock were divided into 2 subgroups based on the direction of the mean frontal place QRS axis: (a) greater than -30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Previous studies. Previous data on the correlation between LAHB and cardiac disease in the general population are scarce (2)(3)(4). Corne et al (2) found a relation with systemic hypertension and cardiac disease in 390 men ages 30 years and over with LAHB compared with an age-and gender-matched control group.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies. Previous data on the correlation between LAHB and cardiac disease in the general population are scarce (2)(3)(4). Corne et al (2) found a relation with systemic hypertension and cardiac disease in 390 men ages 30 years and over with LAHB compared with an age-and gender-matched control group.…”
Section: Discussionmentioning
confidence: 97%
“…Previous data on the correlation between LAHB and cardiac disease in the general population are scarce (2)(3)(4). Corne et al (2) found a relation with systemic hypertension and cardiac disease in 390 men ages 30 years and over with LAHB compared with an age-and gender-matched control group. Studies of the prognostic significance of isolated LAHB in the general population or in subjects without clinical evidence of cardiac disease are limited, but have reported no effect of LAHB on mortality (3,4).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study by Corne et al 48 , conducted on 390 males older than 30 years, reported an increased incidence of CAD in patients with LAHB when compared to the sex-matched controls. Similar studies reported an association between LAHB and the increased risk of cardiac death [49][50][51] .…”
Section: Discussionmentioning
confidence: 97%
“…Left axis deviation may also occur in the absence of apparent cardiac disease and it is not necessarily a sign of significant underlying heart disease [5]. Left axis deviation is relatively common with advancing age even in the absence of clinically overt heart disease and rare during early adult years [17,[28][29][30][31][32][33][34][35][36][37][38][39][40]. In a population-based study of the people 20 years and above, almost half of the people with left axis deviation had isolated left axis deviation without evidence of heart diseases [28].…”
Section: The Isolated Left Anterior Fascicular Conduction Delaymentioning
confidence: 99%